Zones of Agency: Understanding Online Faculty Experiences of Presence - Anita Samuel (Athabasca University Press, 2020)
As instructors are forced to move their courses online, they are confronted by a sense of isolation and distance from their learners. Research has shown that feelings of loneliness are mitigated when presence is created in the online environment. An interpretive phenomenological analysis was conducted at a public university in the United States to answer the question: What are the determinants of presence for instructors in online teaching? Twenty-five online instructors from various disciplines, with diverse levels of experience teaching online, were recruited for the study. Interviews, analysis of course syllabi, and observations of course sites revealed five determinants of presence for online instructors: content, format, strategies, technology, and students. The crucial factor in deciding an instructor’s experience of presence was the degree of agency instructors had over these determinants. This paper introduces the Zones of Agency for Online Instructors model and describes how the model can be used to enhance instructors’ experiences of presence.